(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
The diagnostic evaluation is a process, requiring, from the psychotherapist, several activities in order to proceed a functional analysis. This kind of analysis is critical to select intervention goals and procedures as well as to supply indicators for its further effectiveness evaluation. This study is survey of 20 Brazilian behavioral case studies published, aimed to identify and analyze the main methods used in child evaluation. The studies were first classified, in naturalistic, I, II or III types, considering methodological criteria proposed by Kazdin (1982) to reduce internal validity threats. Then, a descriptive and quantitative analysis of the evaluation methods used was made. Most of the studies (75%) were classified as naturalistic and Type-I studies and the most frequent methods were initial interviews with parents or child and child’s direct observation in therapy, with a smaller proportion of recording techniques and tests. Some possible factors related to the selection of these methods are discussed and research questions suggested.